Is afforestation-induced land use change the main contributor to vegetation dynamics in the semiarid region of North China?. (May 2018) - Wang, Fangtian; An, Pingli; Huang, Can; Zhang, Zhe; Hao, Jinmin
Highlights: Four major land use change progresses were identified in the study area. Vegetation coverage in 10.47% of the study area was significantly influenced by human activities. Afforestation and agricultural intensification can effectively increase vegetation coverage. Agricultural abandonment and cropland degradation led to vegetation degradation. Abstract: Quantitatively analyzing the response of vegetation dynamics to land use change is very important, especially it relates to gaining a better understanding of the effects of ecological restoration projects. Previous studies have focused on the effects of land use change caused by the Grain for Green Project (GGP) on vegetation dynamics, but the effects from other changes in land use have less been explored. Therefore, in order to bridge this gap, Landsat images and MODIS Normalized Difference Vegetation Index (NDVI) data were used to examine how land use had changed from 2000 to 2014 as well as to study its influence on vegetation growth in Ulanqab City, Inner Mongolia, China. For this, four major land use change processes were identified through land use trajectories analysis: the Grain for Green Program (GGP), agricultural intensification, cropland abandonment, and cropland degradation. The GGP caused 36.60% of the total land use change in our study area, while three other processes caused the remaining of 44.40%. Anthropogenic activities significantly influenced vegetation coverage in 10.47% of the research area based on residual trend analysis. Pixels analysis showed 8.72% of the research area experienced a significant increase in vegetation coverage, where 39.53% of this increase was caused by afforestation while 33.25% was attributable to agricultural intensification. However, vegetation degradation was observed in 1.75% of the research area, of which 12.91% was caused by afforestation, an amount that was lower than that caused by the combined effects of the other three practices. Overall, afforestation can effectively increase vegetation coverage, but the overall effects can be undermined by other unstainable land use. However, although agricultural intensification contributed greatly to an increase in vegetation coverage, it also caused severe land degradation. This study demonstrates that ecological restoration projects and regional ecological systems are facing increasing pressure in Ulanqab City caused by an increase in human activity. Managing and maintaining restoration projects sustainably and appropriately in fragile areas will help land managers to achieve better results during vegetation restoration as well as to contribute to sustainable development.